Carrefour enterprise valuation - Lebreiro, Afonso Paisana de Vilas-Boas (2014)
This thesis consists in a global valuation of Carrefour, one of the largest food retailers in the World, using the three most commonly used methods, Discounted Cash Flow (DCF), Economic Value Added – Market Value Added (EVA-MVA) and Multiples. Since Carrefour is present in three continents and more than fifteen countries, studying its historical presence in terms of market position in each country is crucial to understand how a French retailer became one of the largest and most influent companies in food retail industry. The business concepts behind its international expansion and the cultural influence that were imposed in many countries through its marketing strategy were one of the keys to success. Concerning the results of DCF and EVA-MVA Models, they were computed through a projection for the 2013-2017 period, based on a set of assumptions and forecasts that include macroeconomic concepts and financial ratios that support the results achieved. Using DCF Model, the investment decision is to BUY the stock. However the relative valuation shows that Carrefour multiples are bellow its benchmark in every key performance indicator. When compared with other similar companies, the Group also presents lower multiples with the exception of P/E, meanings that Carrefour share may be undervalued.